Solenoids bodies - Cuadra, Manuel (1958)
The "Solenoids Bodies" are known in hematology as "Bodies crescent" in Spanish, "Crescent bodies" in English, "Halbmondkörper" in German and "demi-lune Corps" in French. It has been described an original method of coloring bodies solenoid which is very appropriate for morphological study. This method is also suitable for dyeing erythrocyte stroma. The solenoid bodies originate from erythrocytes and meet your stroma; they are produced in vitro to extend the blood on the slide. Two factors involved in its formation: a mechanical friction factor given by erythrocytes against the glass surface and an essential chemical factor represented by the blood lipids involved increasing the fragility of erythrocytes. The number of bodies in a given solenoid blood extension is directly proportional to its lipid content, whether of exogenous origin (postprandial lipemia) or endogenous origin. The solenoid bodies were also found in the dog, sheep, rabbit, guinea pig, rat and chicken.